(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The Articles departs from the Italian Court of Cassation about a migrant women asking for international protection in light of the denounced exposure to gender-based discrimination if forcibly expelled to her Country of origin. The judgments represents the premise for a wider investigation of the gendered re-reading of the obligations of international protection as emerged from three recent judgements of the European Union Court of Justice. The joint analysis of the investigated and most updated developments of national and supranational case-law offers the chance for an investigation into the implications of the suggested gendered reading of international protection obligations, as a tool to safeguard so-called minority women, as those belonging to minoritarian social groups.